Kisah anbiya’dalam al-Quran: Kajian perspektif pembangunan modal insan berasaskan keusahawanan / Mohd Nasir Ripin - Mohd Nasir, Ripin (2016)
This study is a document analysis on the stories of the prophets in the Holy Quran. The first objective of the study is to identify stories of the prophets on human capital development related to entrepreneurship. Secondly, it tries to clarify the concept of human capital development based on the stories. Third, it aims to explain approaches in developing human capital. Fourth, it tries to differentiate the characteristics of developed human capital (muslihin) as compared to an undeveloped one (mufsidin). And the final objective is to present principles of human capital development in light of entrepreneurship based on the stories of the prophets in the Quran. To achieve these objectives, the study uses the method of Determination of Subjects in three main themes namely; the story of prophets, human capital development and entrepreneurship. The main body of the data collected is based on library reviews which are further supported by interviews. Analysis of the data was conducted through Inductive, Deductive as well as Comparative methods. Among the prophets featured as sample cases are Noah, Hud, Abraham, Lot, Yusof, Moses, David, Solomon, and Muhammad SAW. The study uncovered the two approaches in developing human capital namely; the process and the situational approaches. Results showed that the prophets use a variety of techniques in the process methods such as the environment, motivation, and practical skills. On the other hand, in the situational approach, muslihin methods such as tauheed, knowledgeable, justice and professional were being employed. These criteria vary significantly with the situation of mufsidin who refused the call of prophets because of shirk, unjust and ghaflah. Hence, the study proposes three principles as the fundamentals of human capital development related to entrepreneurship i.e.; concept and framework, process and technique, as well as products and entrepreneurial goals.